Empathic and Agentic Approaches to Community-Engaged Research Scholarship: A Playful, Frugal, and Co-Creative Framework Through the ACES Project in Southeast Asia - Sylvester, Arnab; Katherine, Wimpenny; Alex, Masters; Dominic, Mahon; Jacey Lynn, Minoi; Fitri Suraya, Mohamad (Sage Journals, 2025)
Educational disparities, particularly in remote and rural areas of Southeast Asia remain a critical challenge, especially regarding access to equitable and inclusive quality education. In response, four universities from the UK, Malaysia, Vietnam, and Indonesia came together in the ACES project - A Community-Centred Educational Model for Developing Social Resilience, funded by the UKRI-ESRC under the Global Challenges Research Fund. By leveraging playful and frugal educational design methods within a community-engaged framework, ACES sought to address how university partnership with community stakeholders across local, regional, national, and international contexts could target and collaboratively address educational challenges in a culturally relevant and sustainable manner. This paper discusses the methodological insights of how Community-Engaged Scholarship (CES) and Community-Engaged Research (CER) were combined and integrated through the lens of the ACES project. CES and CER have each been discussed as approaches useful for leveraging and strengthening community research relations with higher education. Collectively referred to as Community-Engaged Research Scholarship (CERS) in this paper, we critique how a collaborative CERS study design was applied to bridge the gap between academic research and community needs by fostering equitable and mutually beneficial partnerships. ACES strategies have focused on how CERS values have been consciously integrated to create impactful educational interventions. Adopting a Case Study approach, the paper analyses initiatives from Indonesia, Malaysia, and Vietnam, mapping the ACES’s core principles—community engagement, playfulness, frugality, and co-creation—to the participatory and community-engaged values of CERS. The findings reveal how ACES served to bridge the urban-rural educational divide, empowering educators and communities to co-create culturally relevant and sustainable learning experiences integrating playful and frugal methods. The CERS design underscores the importance of agile and co-creative pedagogical approaches, especially in the context of crises like the COVID-19 pandemic to enhance the resilience and effectiveness of community-engaged educational initiatives.